(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article considers the issues of determining the rational parameters of cleaning a heap of millet seeds from separated seeds of weeds of mouse and chicken millet on a gravity multi-tiered impact separator. To determine the factors that have the greatest impact on the optimization criteria, an a priori ranking method was applied, and as a result, three main varying factors were identified, the levels of which were assigned based on the results of previous theoretical studies and design considerations. In the experiments, a three-level non-compositional Box-Benkin plan of the 2nd order is chosen. The regression equations were obtained, as a result of which two-dimensional cross-sections of the response surfaces of the optimization parameters were constructed. To ensure the interpretation of the obtained results of the study on the response surface, the method of two-dimensional sections is used. As a result of the graph-analytical analysis of the obtained expressions, the rational parameters of the value of the factors influencing the process of separating hard-to-separate weed seeds were determined.